Optical Losses in Hybrid Microcavity Based in Porous Semiconductors and its Application as Optic Chemical Sensor - Hernández, Claudia Antonio (2019)
In this study the experimental and theoretical optical analysis of a hybrid microcavity (HM) based in porous silicon (PS) and nanoporous anodic alumina (NAA) are presented. The microcavity was centered in the visible region at 760 nm. Distributed Bragg reflector (DBR) was obtained using galvanostatic anodizing method and while NAA by the two-step anodization technique. From SEM micrographs the HM different regions are observed. HM optical characterization in the visible region was done, considering two different light sources, point and non-point respectively. These results reveal a decrease in the quality factor (Q) from 350 to 190 when the source is exchanged; this behavior has been mainly attributed to the light scattering at NAA. Furthermore, it was possible to study Q change, through transmittance simulation using the transfer matrix and Landau-Lifshitz-Looyenga theoretical methods. When a point light source is used, there are no optical losses making possible to sense 1% of analyte resulting in a 0.29 nm redshift of the resonant peak. According with these results we propose to apply the HM as chemical optic sensor.